2017
DOI: 10.1111/1742-6723.12839
|View full text |Cite
|
Sign up to set email alerts
|

Do antiemetic drugs benefit adult emergency department patients with nausea? The literature says no, but is it right?

Abstract: Nausea is a common problem in ED patients. Antiemetic drugs have been used in the ED for decades, but a recent Cochrane review found no convincing evidence for the benefit of antiemetic drugs over placebo. This was largely based on three placebo-controlled trials, which found mean Visual Analog Scale (VAS) changes for various drugs and placebo, to be similar. However, reliance on mean VAS change as the primary outcome measure has probably been a mistake. It does not give information on the number of improved p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
10
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(10 citation statements)
references
References 12 publications
(27 reference statements)
0
10
0
Order By: Relevance
“…The primary objective of antiemetic treatment for ED patients with nausea is clinically significant symptom improvement. Mean group VAS change does not provide direct evidence for this objective . Recent research has demonstrated that ED patients with symptom improvement (“a little less” or “a lot less”) reliably report VAS reductions in excess of –5 mm .…”
mentioning
confidence: 99%
See 4 more Smart Citations
“…The primary objective of antiemetic treatment for ED patients with nausea is clinically significant symptom improvement. Mean group VAS change does not provide direct evidence for this objective . Recent research has demonstrated that ED patients with symptom improvement (“a little less” or “a lot less”) reliably report VAS reductions in excess of –5 mm .…”
mentioning
confidence: 99%
“…Doubts have been expressed about these seemingly counterintuitive findings . Possible limitations of the currently used outcome measures for the detection of real differences and the difficulty of interpreting the main study results have been highlighted …”
mentioning
confidence: 99%
See 3 more Smart Citations